Effect of Lifestyle based Edu Vaccine in Indian community: Study Outcomes of National Program for Prevention and Eradication of Heart Attack (NPPEHA) - Bimal Chhajer, Vikram Singh, Girija Kumari, Roheed Amin, Sachin Tiwari, Pawan Jaiswal, Manish Kumar Gupta (Journal of Applied Pharmaceutical Science, 2020)
Objective: The present study was designed to evaluate the impact of Education (Edu) vaccine in National Program for Prevention and Eradication of Heart Attack (NPPEHA).Methods: This pretest–posttest designed study was held in the SAAOL Heart Center in different cities (Delhi, Kolkata, Bangalore, and Mumbai) of India from Nov 2016 to Dec 2017. Total 6,225 community people were enrolled. An educational counseling intervention (Edu vaccine) comprising: knowledge of heart, heart disease awareness, risk factor awareness, preventive measure awareness and diagnostic, and regular medical checkups were given to community people with expert doctors through face-to-face interactions and video counseling. The effect of lifestyle-based counseling was assessed through pre- and post-designed Edu vaccine questionnaire.Results: The results of this study showed a significant improvement in knowledge of heart (79.6%), heart disease awareness (87.8%), risk factor awareness (74.9%), preventive measure awareness (89.8%), diagnostic, and regular medical checkups (84.7%), respectively.Conclusion: The results of this study showed a significant improvement in knowledge of heart (79.6%), heart disease awareness (87.8%), risk factor awareness (74.9%), preventive measure awareness (89.8%), diagnostic, and regular medical checkups (84.7%), respectively. The first phase study of NPPEHA results conclude that lifestyle-based Edu vaccine is effective, and this tool is very easy to follow and heart attack prevention methods. The next phase of NPPEHA program is ongoing and results are awaited.
Keywords: NPPEHA, coronary artery disease, heart attack, Edu vaccine, SAAOL heart center.